Transformasi Kewenangan Peradilan Agama Pasca Undang - Undang Perkawinan Tahun 1974 - Achmad Rizky Airlangga; Faiq Muhammad Zufar; Syahputra Aditya Kusrin Surbakti (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
The authority of the Religious Courts in Indonesia has undergone substantial transformation since the enactment of the 1974 Marriage Law, which serves as a foundational milestone in harmonizing the national legal system on family matters. Prior to this legislation, the jurisdiction of the Religious Courts was limited and influenced by legal dualism among customary law, Islamic law, and Western civil law inherited from the colonial period. This article examines how the Marriage Law initiated a shift in the structure and legitimacy of the Religious Courts and how their jurisdictional expansion reached a more comprehensive form through Law No. 7 of 1989 on Religious Courts and its subsequent amendments under Law No. 3 of 2006 and Law No. 50 of 2009. Using a normative juridical approach, this study analyzes statutory regulations, academic literature, and Islamic legal doctrines. The findings show that the Marriage Law provided the initial legal foundation for strengthening the Religious Courts' authority in handling family disputes, which was later expanded significantly to include inheritance, wills, grants, endowments (wakaf), alms (zakat), charitable donations (infaq and sadaqah), and Islamic economic matters during the legal reform era. This transformation not only reinforced the institutional structure of the Religious Courts but also improved access to justice for Muslim communities and supported the integration of Islamic law into Indonesia’s national legal framework. Therefore, the development of the Religious Courts’ authority after the Marriage Law reflects the dynamic modernization of the legal system and the harmonization between religious values and the rule of law in Indonesia.